HUBUNGAN PEMBELAJARAN BERBASIS PROYEK DALAM MEWUJUDKAN PEMBELAJARAN ABAD 21 PADA SISWA KELAS IV SDN TAMANSARI II - Mustika Kirana Putri; Didit Yulian Kasdriyanto; Ribut Prastiwi Sriwijayanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to determine the relationship between project-based learning in realizing 21st century learning in grade IV students of SDN Tamansari II. In this study, the research design used a quantitative approach with a pre-experimental one group pretest posttest design. The population in this study were all grade IV students of SDN Tamansari II in the 2024/2025 academic year with a sample size of 20 students. Data collection in this study used a pretest and posttest which functioned to determine student learning outcomes before and after being treated. The study was conducted by testing the hypothesis using the "T" test which considered the prerequisite test, namely the normality test. Based on the results of the study with descriptive statistical analysis, the pretest score obtained an average of 60 with a standard deviation of 20.51957 and the posttest obtained an average of 95 with a standard deviation of 10.25978. then after the T-test was conducted, it was found that there was a relationship between project-based learning in realizing 21st century learning. It was stated that the T-test (paired sample t test) with the results obtained tcount> ttable with a level of 5% so that 14,457> 1,729 and a significance of 0.001 <0.05. So it can be stated that Ha is accepted that there is a relationship between project-based learning in realizing 21st century learning in grade IV students of SDN Tamansari II.